Board Gender Diversity, Corporate Reputation and Market Performance - Larkin, Meredith B.; Bernardi, Richard A.; Bosco, Susan M. (Universiti Utara Malaysia, 2012)
This study examines the association between corporate transparency, ethical orientation of Fortune 500 companies, the number of females represented on the board of directors as reported in the 2010 annual report data and respective stock performance. Our basis for this judgement was whether the firm was listed on either (both) Ethisphere Magazine’s 2010 ‘World’s Most Ethical Companies’ or (and) Corporate Responsibility Magazine’s 2010 ‘100 Best Corporate Citizens List’. Our results indicate that, as the number of women directors increased, the probability of a corporation appearing in these lists increases. Finally, while being on one of these lists did not increase corporate return data in a statistically significant sense, it did dramatically reduce the degree of negative returns.